2020
DOI: 10.1371/journal.pone.0231872
|View full text |Cite
|
Sign up to set email alerts
|

The impact of an integrated depression and HIV treatment program on mental health and HIV care outcomes among people newly initiating antiretroviral therapy in Malawi

Abstract: Background Depression is highly prevalent among patients newly starting antiretroviral treatment (ART) in Malawi and many other countries. Untreated depression at ART initiation can disrupt the HIV care continuum. Effective approaches for depression screening and treatment exist for low-resource settings, but they are rarely applied. Identifying effective implementation strategies are critical. Methods A pilot program integrated depression screening and treatment into routine HIV care using existing staff at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 64 publications
(112 reference statements)
1
58
0
Order By: Relevance
“…The study’s total sample size ranged from 32 to 1140, intervention sample sizes ranged from 19 to 578 and control group sample sizes ranged from 13 to 562. The majority of studies (n = 22, 73.33 %) reported on interventions for depression [33‐55]. Major depressive disorder was confirmed using diagnostic interviews such as SCID or MINI in three studies [34‐36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study’s total sample size ranged from 32 to 1140, intervention sample sizes ranged from 19 to 578 and control group sample sizes ranged from 13 to 562. The majority of studies (n = 22, 73.33 %) reported on interventions for depression [33‐55]. Major depressive disorder was confirmed using diagnostic interviews such as SCID or MINI in three studies [34‐36].…”
Section: Resultsmentioning
confidence: 99%
“…Other pharmacological interventions had no benefit over placebo. This review also revealed a single study which evaluated fluoxetine in combination with problem‐solving therapy where the intervention did not have significant effects [43].…”
Section: Resultsmentioning
confidence: 99%
“…Elevated depressive symptoms suggesting a high risk of a depressive disorder (hitherto described as "depression") was defined as a PHQ-9 score ≥ 5 at ART initiation, following the definition in the parent study [40]. We also consider a 3-level categorical depressive severity measure (0-4, 5-9, and ≥ 10, corresponding to no, mild, and moderate to severe depression, respectively).…”
Section: Depression At Art Initiationmentioning
confidence: 99%
“…9 This was supported by previous literature in which HIV patients who were stable and on ART may have benefited from intervention by healthcare workers that lead to decreased HIV related stressors over time. 9,15,32,33 Indeed, it is necessary to provide ongoing mental health monitoring of HIV patients at different levels of the healthcare intervention, and special emphasis is recommended for those newly identified HIV positive people.…”
Section: Discussionmentioning
confidence: 99%